(untitled) (Revista INTEREDU11, 2024)
The purpose of the article is to provide solid foundations for a proposal to improve the policy and instruments of free studies in higher education for Chile, in force for some years, which from the perspective of equity demands substantive transformations in dimensions such as the institutional accreditation processes that impact -among others- on this situation. Based on background information on the aforementioned topic, the problem in question is analyzed and proposals on this matter are derived. In line with the spirit of this initiative, adaptation options are presented that are relevant, taking into account the problems of student retention, social segregation and economic returns that the Chilean higher education system currently shows and, also due to the great financial sus-tainability difficulties of this policy that are already visible in the short term and even more so in the long term.